Definition of Hyperbole (Journal of Pedagogical Inventions and Practices, 2022)
Hyperbole is a figure of speech and literary device that creates heightened effect through deliberate exaggeration. Hyperbole is often a boldly overstated or exaggerated claim or statement that adds emphasis without the intention of being literally true. In rhetoric and literature, hyperbole is often used for serious, comic, or ironic effects.